(untitled) (Sindoro: Cendikia Pendidikan, 2025)
Children who live and grow up in orphanages are part of a group vulnerable to various psychosocial problems, ranging from difficulty adapting and socializing, low self-confidence, trauma problems originating from their background. So this study aims to analyze the effectiveness of the group guidance method for children living in orphanages applied by social workers at the “Karya Ramlan” Orphanage. This approach is used by reviewing from the planning of the group guidance method to its evaluation. The success of this program is also inseparable from the important role of facilitators, orphanage administrators, and also a supportive environment. This study confirms that group guidance is an effective way to support orphanage children in overcoming psychosocial.